Antibiotic Prescribing in Children Hospitalized With COVID-19 and Multisystem Inflammatory Syndrome in Spain: Prevalence, Trends, and Associated Factors. Issue 5 (21st February 2022) - Aguilera-Alonso, David; Epalza, Cristina; Sanz-Santaeufemia, Francisco José; Grasa, Carlos; Villanueva-Medina, Sara; Melendo Pérez, Susana; Cervantes Hernández, Eloísa; Urretavizcaya-Martínez, María; Pino, Rosa; Gómez, Marisa Navarro; Orive, Javier Pilar; González Zárate, Ana; et al.
Abstract: The SARS-CoV-2 pandemic has caused an increase in antibiotic use in different settings. We describe the antibiotic prescribing prevalence, associated factors and trends, as well as concomitant bacterial infections in children hospitalized with COVID-19 or multisystemic inflammatory syndrome related to SARS-CoV-2 in Spain.